2016
DOI: 10.1039/c6ra09289f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly branched poly(δ-valerolactone)s: a comparative study between comb and linear analogues

Abstract: A structure–property relationship was constructed based on the facile synthesis of linear-comb and star-comb poly(δ-valerolactone)s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…The DSC thermograms of pure PDVL and PDVL/TiO2 nanocomposites recorded in the cooling mode are shown in Figure 5, and the temperatures and the heats of crystallization that were deducted are gathered in Table 2. The DSC thermogram of pure PDVL exhibits a crystallization temperature at 27 °C, which is slightly lower than that in the literature (29.7-30.4 °C) [44]. However, no significant change in the Tc value of PDVL is observed when the amount of TiO2 varied from 1 to 5 wt % is incorporated in the polymer matrix.…”
Section: Thermal Behavior Of the Pdvl/tio 2 Nanocompositecontrasting
confidence: 57%
See 1 more Smart Citation
“…The DSC thermograms of pure PDVL and PDVL/TiO2 nanocomposites recorded in the cooling mode are shown in Figure 5, and the temperatures and the heats of crystallization that were deducted are gathered in Table 2. The DSC thermogram of pure PDVL exhibits a crystallization temperature at 27 °C, which is slightly lower than that in the literature (29.7-30.4 °C) [44]. However, no significant change in the Tc value of PDVL is observed when the amount of TiO2 varied from 1 to 5 wt % is incorporated in the polymer matrix.…”
Section: Thermal Behavior Of the Pdvl/tio 2 Nanocompositecontrasting
confidence: 57%
“…• were assigned to diffraction of the (110) and (200) lattice planes, respectively [44], indicating that the PDVL probably crystallized in the ordinary crystal geometric structure. The crystallographic analysis conducted by Furuhashi indicated that PDVL crystallized with an orthorhombic unit cell structure [45].…”
Section: Xrd Analysismentioning
confidence: 99%
“…Poly(δ-valerolactone) (PVL) has identical features with linear aliphatic polyester poly(ε-caprolactone) (PCL), such as hydrophobic nature, semi-crystalline structure, low melting point and low cytotoxicity. However, there are limited studies on synthesis and application of PVL in biomedical area in contrast to PCL [4,6]. There exist several attempts for ring opening polymerization (ROP) of δ-valerolactone (δ-VL) including organometallic catalysts or biocatalyts.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, synthesis of PVL with maximum molecular weight and suitable properties was purposed. Thus, polymerizations were carried out at varied temperatures (30, 40, 60, and 80℃) and periods (6,24,48,72, and 120 hours) in order to determine optimum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The NMR spectra of PVL is shown in Figure . Each characteristic peak of the proton is detected and allocated, conform to the structure of PVL described in previous reports . The methylene signal of PVL is observed around 4.17 ppm while the other chemical peaks of PVL were observed around 2.44, and 1.78 ppm respectively confirming the formation of PVL.…”
Section: Resultsmentioning
confidence: 99%